Acanthamoeba and Stenotrophomonas maltophilia keratitis with fungal keratitis in the contralateral eye - Thomas F Mauger (Dove Medical Press, 2010)
Thomas F Mauger, Rebecca Ann Kuennen, Reynell Harder Smith, William SawyerDepartment of Ophthalmology, The Ohio State University, Columbus, OH, USAPurpose: The purpose of this study is to describe the diagnosis, course, and outcome of a case of Acanthamoeba and Stenotrophomonas keratitis with a fungal keratitis in the contralateral eye.Methods: A case of Acanthamoeba and Stenotrophomonas keratitis was diagnosed with confocal microscopy and cultures with confocal diagnosis of fungal keratitis in the fellow eye.Results: During the initial treatment of the Acanthamoeba and Stenotrophomonas keratitis, the contralateral eye developed a keratitis that demonstrated hyphae in the corneal stroma with confocal microscopy consistent with fungal keratitis.Conclusions: Bilateral chronic keratitis cannot be assumed to be caused by the same organism and independent cultures, and confocal microscopy needs to be performed to direct appropriate therapy.Keywords: Acanthamoeba, Stenotrophomonas, confocal, fungus, keratitis